Using Drones and Robots for Social Distancing: Literature Review, Challenges and Issues - Murad S.S.; Badeel R.; Ahmed R.A.; Yussof S. (Institute of Electrical and Electronics Engineers Inc., 2025)
Since the number of recorded instances of COVID-19 and the number of deaths linked with the virus are both on the rise, it is crucial to maintain an appropriate level of social distance and wear masks to prevent the transmission of coronavirus. The goal of the Social Distancing is to determine if a given pair of persons is keeping a suitable amount of space from one another. Quarantining infected areas and limiting the spread of viruses in both social and physical settings have been made easier with the help of a number of promising robotic technologies that aid people and healthcare experts in the tracking of virus symptoms, the care of infected individuals, and the avoidance of further infection and spread. In this study, we examine the most up-to-date strategies, structures, and tools for utilizing drones in non-social contexts. Additionally, difficulties, problems, and restrictions within the existing literature are addressed. The primary goal of this study is to aid and educate developers and readers interested in deploying drones and robots' technology to battle COVID-19, and to expose the challenges observed in the previous studies to allow the researcher to improve their methods and systems. ? 2024 IEEE.